Ecological Justice in Islamic Family Law: Integrating Maqasid al-Shari'ah with Environmental Ethics in Post-Pandemic Societies - Wahyudi, Bambang; Nabilah binti Yusof; Rahmatul Fadhil; Dody Sulistio; Achmad Yani (Tuah Foundation, 2025)
This study addresses a critical gap in Islamic legal discourse: the marginalization of ecological justice (ʻadālat al-bīʻah) within Islamic family law, despite the family’s central role in shaping consumption, education, and environmental ethics. The post-pandemic era has intensified this urgency, as lockdowns revealed both heightened household waste and increased dependence on local ecosystems, prompting a reevaluation of domestic responsibility under sharī‘ah. Drawing on Jasser Auda’s maqāṣid al-sharīʻah, Robert D. Bullard’s environmental justice theory, and Donna Haraway’s ethics of care, this research develops fiqh al-istiqlāl al-bīʻī—a jurisprudence of ecological autonomy rooted in the family. Using qualitative-descriptive methods, primary sources include MUI fatwas (41/2014, 04/2014), national environmental reports, and policy documents, analyzed through textual and contextual frameworks. Findings show that ḥifẓ al-bī’ah must be recognized as a sixth maqṣad (maqṣad sādis), as ecological degradation now directly threatens ḥifẓ al-nafs, al-nasl, and al-māl. Marginalized families in mining regions like Bangka Belitung and Kalimantan exemplify ḍarar majmū‘ - cumulative harm from environmental injustice and juristic neglect. The pandemic underscored the fragility of supply chains and overconsumption, offering a transformative lesson: the bayt (household) must become a khalīfah fī al-bayt, a stewardship unit grounded in zuhd and iḥsān. This integration positions the Muslim family not merely as a legal entity but as an agent of systemic change. While limited to Indonesian data, the framework invites cross-national application. Future research should explore ecological waqf and green marriage contracts as legal instruments. Ultimately, reforming Islamic family law into a vehicle for ecological justice is no longer optional but a normative imperative in the Anthropocene.